Christian-Muslim Relations. A Bibliographical History. Volume 12 Asia, Africa and the Americas (1700-1800) - Thomas, David,; Chesworth, John A., (The History of Christian-Muslim Relations, 2018)
Christian-Muslim Relations, a Bibliographical History 12 (CMR 12) covering the Middle East, South and Southeast Asia, Africa and the Americas in the period 1700-1800 is a further volume in a general history of relations between the two faiths from the 7th century to the early 20th century. It comprises a series of introductory essays and also the main body of detailed entries which treat all the works, surviving or lost, that have been recorded. These entries provide biographical details of the authors, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between numerous leading scholars, CMR 12, along with the other volumes in this series, is intended as a basic tool for research in Christian-Muslim relations. Section Editors: Clinton Bennett, Luis F. Bernabe Pons, Jaco Beyers, Emanuele Colombo, Karoline Cook, Sinéad Cussen, Lejla Demiri, Martha Frederiks, David D. Grafton, Stanisław Grodź, Alan Guenther, Emma Gaze Loghin, Gordon Nickel, Claire Norton, Reza Pourjavady, Douglas Pratt, Radu Păun, Charles Ramsey, Peter Riddell, Umar Ryad, Mehdi Sajid, Cornelia Soldat, Karel Steenbrink, Ann Thomson, Carsten Walbiner